Philippines : Poverty Assessment, Volume 2. Methodology - World Bank (Washington, DC, 2013)
This report is intended as an input into the Philippine Government's poverty eradication strategy. The report aims to update our understanding of the nature of poverty and the recent progress in poverty reduction in the Philippines. It examines the extent to which growth in the nineties has translated into poverty reduction and analyzes how well publicly-provided social services reach the poor and whether redistributive policies attain their objectives. The report also focuses on the social impact of the recent financial/El Nino crises and explores policies to reduce vulnerability in the Philippines. The report comprises two volumes. The main volume starts with a summary of the profile of the poor and trends in poverty. It then proposes a framework for attacking poverty built on three pillars: 1) promoting opportunity for poor people through generating broad-based growth and building up the assets of the poor; 2) enhancing security of poor people through reducing vulnerability and helping the poor manage risks; and 3) facilitating empowerment of poor people to ensure accountable institutions. Finally, the main report examines the information base for pro-poor policies and offers suggestions for future work. The second volume provides the detailed analytical basis for many of the findings presented in the main report.